Early mortality of stage IV non-small cell lung cancer in the United States. (3rd August 2019) - Amini, Arya; Verma, Vivek; Glaser, Scott M.; Shinde, Ashwin; Sampath, Sagus; Stokes, William A.; Rusthoven, Chad G.; Massarelli, Erminia; Salgia, Ravi; Gaspar, Laurie E.; Liu, Arthur K.
Abstract: Background : Early mortality is a major deterrent to oncologic management, often preventing delivery of therapy or leading to administration of treatment that offers limited benefit from aggressive interventions. Due to more recent progress in therapeutic options for stage IV non-small cell lung cancer (NSCLC) patients, identifying those at high risk of early mortality (within 30 days) could have implications for treatment selection. Because early mortality following diagnosis of metastatic non-small cell lung cancer (NSCLC) is not well-characterized, this investigation evaluated national trends and predictors thereof. Material and methods: The National Cancer Database was queried for cases of pathologically confirmed metastatic NSCLC with complete vital status and clinical information, diagnosed between 2006 and 2014. Multivariable logistic regression ascertained factors associated with 30-day mortality. Results: Of 346, 681 patients, 45, 861 (13%) experienced early mortality over the past decade, which remained relatively constant over time. Predictors of early mortality included advancing age (>65 years), male gender, Caucasian race, non-private insurance, lower income, greater comorbidities, residence in metropolitan and/or lesser-educated areas, treatment at community centers, patients with no prior history of cancer and regional differences ( p < .01 for all). Early mortality was highest in patients older than 80 years with multiple comorbidities (29%). The majority of patients (71%) who died within 30 days did not receive any therapy. Conclusions: A fair proportion of NSCLC patients experience early mortality, which has not decreased over time. The majority of patients with early mortality do not receive treatment. Prognostic factors for early mortality should be considered during initial evaluation and subsequent follow-up of these patients. Doing so may impact systemic treatment selection by medical oncologists, management of (oligo)metastatic disease by radiation and surgical oncologists and cost-effective administration of these therapies in the stage IV NSCLC population.